Epigallocatechin-3-gallate inhibit replication of white spot syndrome virus in Scylla paramamosain. Issue 67 (August 2017) - Wang, Zhi; Sun, Baozhen; Zhu, Fei
Abstract: Epigallocatechin-3-gallate (EGCG) has exhibited potential antibacterial and anticancer activities. In this study, we tested whether EGCG can protect the mud crab Scylla paramamosain against white spot syndrome virus (WSSV). Treatment with 1.5 mg/kg EGCG killed crab hemocytes but treatment with 1 mg/kg EGCG did not. Results of the virus challenge experiment confirmed that EGCG could enhance the survival rate of WSSV-challenged crabs, and treatment with 1 mg/kg EGCG significantly increased their resistance to WSSV compared with the control. Thus, 1 mg/kg EGCG was used as the experimental dose in subsequent analyses. EGCG treatment may induce certain immune pathways, such as the phenoloxidase and JAK-STAT pathways, and it also can enhance the activity of prophenoloxidase. EGCG + WSSV treatment significantly reduced the number of WSSV copies at 24, 48, and 72 h post-challenge compared with the control (WSSV challenge without EGCG treatment). These results demonstrate that EGCG may effectively improve innate immunity and survival of WSSV-challenged S. paramamosain and inhibit WSSV replication by blocking the expression of late stage WSSV genes. Therefore, our study presented that EGCG might represent a new potential therapeutic or preventive approach to control white spot syndrome. Highlights: EGCG treatment may induce phenoloxidase and JAK-STAT pathways, and enhance the activity of prophenoloxidase in crabs. EGCG treatment significantly reduced the number of WSSV copies in crabs. EGCG could enhance the survival rate of WSSV-challenged crabs.